Genetic alterations within the DENND1A gene in patients with polycystic ovary syndrome (PCOS). - Mette B Eriksen (Public Library of Science (PLoS), 2013)
Polycystic ovary syndrome (PCOS), the most common endocrine disease among premenopausal women, is caused by both genes and environment. We and others previously reported association between single nucleotide polymorphisms (SNPs) in the DENND1A gene and PCOS. We therefore sequenced the DENND1A gene in white patients with PCOS to identify possible alterations that may be implicated in the PCOS pathogenesis. Patients were referred with PCOS and/or hirsutism between 1998 and 2011 (n = 261). PCOS was diagnosed according to the Rotterdam criteria (n = 165). Sequence analysis was performed in 10 patients with PCOS. Additional patients (n = 251) and healthy female controls (n = 248) were included for SNP genotyping. Patients underwent clinical examination including Ferriman-Gallwey score (FG-score), biochemical analyses and transvaginal ultrasound. Mutation analysis was carried out by bidirectional sequencing. SNP genotyping was tested by allelic discrimination in real-time PCR in the additional patients and controls. Sequencing of the DENND1A gene identified eight SNPs; seven were not known to be associated with any diseases. One missense SNP was detected (rs189947178, A/C), potentially altering the structural conformation of the DENND1A protein. SNP genotyping of rs189947178 showed significantly more carriers among patients with PCOS and moderate hirsutism compared to controls. However, due to small sample size and lack of multiple regression analysis supporting an association between rs189947178 and FG-score or PCOS diagnosis, this could be a false positive finding. In conclusion, sequence analysis of the DENND1A gene of patients with PCOS did not identify alterations that alone could be responsible for the PCOS pathogenesis, but a missense SNP (rs189947178) was identified in one patient and significantly more carriers of rs189947178 were found among patients with PCOS and moderate hirsutism vs. controls. Additional studies with independent cohort are needed to confirm this due to the small sample size of this study.